PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MODEL INKUIRI TERBIMBING UNTUK SISWA KELAS V MI DARUSSALAM MALANG - muafi, Achmad (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
This research was motivated by the lack of learning media at the MI Darussalam Malang school. This problem results in a decrease in the level of student learning activity and also students' understanding of the material, especially in science subjects. The objectives of this research and development are to (1) develop learning media for Student Worksheets (LKPD) on homogeneous and heterogeneous mixed substance material, (2) assess the feasibility of the product to determine whether there is an increase in understanding of concepts on homogeneous and heterogeneous mixed substance material, and ( 3) find out students' responses regarding the attractiveness of the Student Worksheet (LKPD) learning media. This type of research is Research and Development (R&D). The model in this development is a model using the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. This research uses the Guided Inquiry development model. The results of the learning media validation were validated by 3 validators with an average percentage of 3.40 for design validation, 3.44, for material validation, and 3.65, for learning validation. 3.49 is the total percentage result for the